Mentoring in Proposing Prima3 Food Safety Certification to Business Actors and Farmers in the Sembalun Area - Muhammad Sarjan; Moh. Taufik Fauzi; Ruth Stella Thei; Kisman Kisman; Achmad Fajar Narotama Sarjan (Pascasarjana Universitas Mataram, 2023)
So far, in the Sembalun area, business actors or agribusinesses of fresh food from plants such as vegetables and fruit have not yet made maximum efforts to obtain safe products for consumption, because they are very dependent on excessive chemical inputs. Likewise, few people in general care about Prima3 or Prima2 certification, because there has not been any socialization of the importance of this certification. Therefore, in this activity, it is necessary to provide assistance in preparing applications for Prima 3 and Prima 2 PSAT food safety certification, so that the number of people doing PSAT and domestic product businesses (rice, corn and other foods in storage) increases. The method used in this activity is the Action Research Method by applying a Participatory Action Program approach from participants through discussion and group work in all activities. The stages in this activity include preparation stages, including problem identification, then a basic survey using exploratory descriptive methods. The activity results show that farmers' assistance in preparing to apply for PSAT, Prima3 and Prima2 food safety certification in the Sembalun area is felt to be very important. Farmers and business groups feel motivated to develop alternative techniques for healthy agricultural cultivation to obtain PSAT products that are safe for consumption. Good horticultural practices to produce safe PSAT products for consumption are considered very important in the Sembalun area. Farmers actually understand the need for efforts to reduce the use of synthetic chemical inputs, both fertilizers and pesticides, in horticultural cultivation to produce products that are safe for consumption. For the continuation of extension activities and its follow-up, it is necessary to continue to provide assistance to farmers and groups of fresh plant origin food (PSAT) entrepreneurs from the Food Security Service, so that the number of prima 3 and prima 2 certificates will increase in the Sembalun area.